A Study of Iterative Signal Processing Schemes for Double-Layered Bit-Patterned Recording - Anawin Khametong; Chanon Warisarn (My University, 2024)
To enhance the areal recording density of the alternated magnetic recording technologies, we have investigated the performances of the iterative recording schemes based on a double-layered bit-patterned magnetic recording (BPMR). We developed a read/write channel model that ideally integrates the signals from both upper and lower layers. In this study, we considered a two-layer recording that uses a single reader to retrieve a single readback signal through a signal combination produced from the upper and lower layers. For signal processing, we initially recover the upper layer signal and subsequently recover the lower layer signal using partial equalization and readback reconstruction schemes where the reproduced readback signals were generated under the iterative system. Based on the results, the proposed iterative signal processing schemes have been certified to deliver better bit error rate performance compared to single-layer BPMR systems, when they were considered at the total areal density of 4 Tb/in2.
Keywords: Iterative Learning Control Systems; Industrial Vision Systems and Defect Detection; Neural Networks and Applications